The effect of transcutaneous electrical nerve stimulation (TENS) on decreasing primary dysmenorrhea pain in adolescents - Nur Rahmawati Sholihah; Ratih Kumorojati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Dysmenorrhea is medical condition indicated by an increase of the prostaglandin (PG) F2-alpha hormone and cyclooxygenase (COX-2) causing hypertonic as well as vasoconstriction activity to the myometrium. It leads to ischemia and stimulating pain in the uterine organs. The condition influence quality of life and productivity of majority female patients. Dysmenorrhea incidence in Indonesia is reported by 64.25% and a total of 52% of students in Yogyakarta experienced drop activity during menstruation. Objectives: This study aimed to evaluate the effect of TENS in reducing primary dysmenorrhea pain among female adolescents in General Ahmad Yani University YogyakartaMethods: A quasi experiment study with pretest-posttest control group design was conducted. A total of 24 participants for intervention and control group were recruited. In order to recruit study participants, this research implemented a quota sampling approach. Primary dysmenorrhea pain measured using Numerical Rating Scale (NRS) and bivariate analysis between both groups carried out using T-test.Results: A significant difference (p<0.05) reported from both groups before and after the intervention. Prior to the treatment, the average pain score for intervention group was 6 (1.70) and ranging from 4-10. After the treatment being delivered, the intervention group experienced lower pain intensity by average 3.42 (1.6) between 1-6 score range. Control group in this study reported average pain score before the intervention by 4 (1.16) with and ranging from 3-6. The treatment decreased control group participants pain level to average 1.50 (0.52) between the range of 1-2. TENS is effective for severe pain management. Effleurage massage suitable for moderate level pain management. TENS intervention effective to lower pain by 3.50%.Conclusions: TENS and massage intervention potential to decrease pain intensity of primary dysmenorrhea. This study reported lower pain level associated with TENS by 3.50%. TENS had significant effect for reducing dysmenorrhea pain by 3.50%.